Child Neglect Crime Based on Law Number 35 of 2014 - Riza, Muhammad; Aspan, Henry; Riza Zarzani, T. (PT. Multidisciplinary Press Indonesia, 2024)
Every child has dignity that should be upheld, and every child born must receive their rights without the child asking. The act of neglecting a child is a criminal act, because this act does not reflect the humanistic side of humans themselves and violates the law. For children, legal protection is a priority because children tend not to be able to become complete individuals. Child protection is carried out to create conditions so that every child can fulfill their rights and obligations for the child's natural, physical, mental and social growth and development. Child protection is also an embodiment of justice in a society, so child protection is sought in various areas of state and social life.